A biology teacher - a second career choice - Tomažič, Iztok (Acta biologica slovenica, 2009)
For several years now, Slovenia has been facing a shortfall of interest in science studies. Some argue that the principal reason for this lies with inadequately trained science teachers in primary and secondary schools. We setout to find the reasons why double degree students of biology (Chemistry-Biology or Biology-Home Economics) at the Faculty of Education chose to become biology teachers, and outline certain guidelines for pedagogical work with students. The results of our survey show that the numberof secondary school graduates whose first choice is either of the two biology teacher study programmes at the Faculty of Education is declining. Students who selected the programme as their second choice are mainly those who did not have enough credit points for their first options, i.e. medicine, dentistry, biochemistry, veterinary sciences or biology at the Biotechnical Faculty. Most of the students who decide to become biology teachers are female. The main motives are the students' fondness for biology and the desire to work with children. Students (regardless of which study programme they select) have fairly similar views on teaching biology. They believe that teachers should introduce practical work in the classroom, have good relationships with students, and are experts in their field (biology). Students in general did not provide innovative ideas about teaching methods which would not be boring or uninteresting. Their ideas reflect their own experience of teachers, which is why it is important that they are included inwork with pupils as early as possible. In this way they can gain their own direct experience of teaching, which helps them to build their own unique ideaof what a biology teacher should be. (Abstract truncated at 2000 characters)
Keywords: Ankete; Biologija; Biology; Education; Poučevanje; Questionnaires; Students; Študenti; Teaching